On lower bound for W (K2n) - Rafael R. Kamalian; Petrosyan, Petros (Изд-во НАН РА)
The lower bound W(K2n) ¸ 3n > 2 is proved for the greatest possible number of colors in an interval edge coloring of the complete graph K2n.
Keywords: Mathematics; Graph theory